The Impact of Hybrid Learning on Students’ Motivation and Academic Achievement in the Digital Era in Improving the Quality of Education - Fauzi, Moh. Ali; Roni Harsoyo (Yayasan Dinamika Ilmu Banyuwangi, 2025)
Hybrid learning has become a solution to address the significant changes in the education system caused by the COVID-19 pandemic. This study aims to analyze the impact of Hybrid Learning on student motivation and academic achievement. Hybrid Learning, which combines face-to-face and online learning, is seen as an approach that can enhance the learning experience for students. The regression test results show that Hybrid Learning has a positive and significant impact on both variables, namely motivation and academic achievement. The regression coefficient for student motivation is 0.580, and for academic achievement, it is 0.740, with a p-value of 0.000 indicating the significance of this impact. The coefficient of determination (R²) for motivation is 0.72, indicating that the model explains 72% of the variation in student motivation, while the R² for academic achievement is 0.75, showing the contribution of Hybrid Learning to improving students' academic performance. Based on the findings, it is recommended that more schools adopt Hybrid Learning, ensuring adequate technological infrastructure and teacher training. A curriculum that supports this model should also be developed to allow students easy access to learning materials. Furthermore, teaching methods should be more interactive, and further research should be conducted to explore other factors affecting the effectiveness of Hybrid Learning. Overall, Hybrid Learning can be an effective strategy to enhance student motivation and academic achievement, provided it is implemented correctly so that it can improve the quality of education.